Requirements Engineering for Safety-Critical Systems: An Interview Study with Industry Practitioners - Martins, Luiz Eduardo G.; Gorschek, Tony (IEEE transactions on software engineering, 2020)
We have conducted in-depth interviews with experienced practitioners in the Safety-Critical Systems (SCS) domain in order to investigate several aspects related to requirements specification and safety analysis for SCS. We interviewed 19 practitioners from eleven SCS companies in different domains with the intention of verifying which approaches they use day-to-day, and what their perceptions are in relation to the approaches used to elicit, analyze, specify and validate safety requirements. The aim of this study is to obtain an in-depth understanding of how requirements engineering is carried out in companies that develop SCS.